2017
DOI: 10.18632/oncotarget.19135
|View full text |Cite
|
Sign up to set email alerts
|

GLUT1 expression in pediatric adrenocortical tumors: a promising candidate to predict clinical behavior

Abstract: BackgroundDiscrimination between benign and malignant tumors is a challenging process in pediatric adrenocortical tumors. New insights in the metabolic profile of pediatric adrenocortical tumors may contribute to this distinction, predict prognosis, as well as identify new molecular targets for therapy. The aim of this work is to characterize the expression of the metabolism-related proteins MCT1, MCT2, MCT4, CD147, CD44, GLUT1 and CAIX in a series of pediatric adrenocortical tumors.MethodsA total of 50 pediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…[25] Furthermore, Pinheiro's work revealed that GLUT1 overexpression was a promising candidate to predict clinical behavior in pediatric adrenocortical tumors. [26] This study suggests the potential role of GLUT1 in a metabolic remodeling towards a hyperglycolytic phenotype in this malignancy. [26] Therefore, the alteration of tumor metabolism after GLUT1 was up-regulated needs to be further investigated.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…[25] Furthermore, Pinheiro's work revealed that GLUT1 overexpression was a promising candidate to predict clinical behavior in pediatric adrenocortical tumors. [26] This study suggests the potential role of GLUT1 in a metabolic remodeling towards a hyperglycolytic phenotype in this malignancy. [26] Therefore, the alteration of tumor metabolism after GLUT1 was up-regulated needs to be further investigated.…”
Section: Discussionmentioning
confidence: 86%
“…[26] This study suggests the potential role of GLUT1 in a metabolic remodeling towards a hyperglycolytic phenotype in this malignancy. [26] Therefore, the alteration of tumor metabolism after GLUT1 was up-regulated needs to be further investigated.…”
Section: Discussionmentioning
confidence: 89%
“…The final scores for ZNRF3 and β-catenin expressions levels were taken as the sum of both parameters (extent and intensity) and grouped into low expression levels (scores of 0–2) and high expression levels (scores of 3–7) as previously reported [ 99 , 102 ]. β-catenin expression in the different cellular localizations (membranous versus cytoplasmic and/or nuclear) was evaluated separately [ 102 , 103 , 104 ] ( Table 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Also, intensity of staining was scored semi-qualitatively as follows: 0: negative; 1: weak; 2: intermediate; and 3: strong. The final score was defined as the sum of both parameters (extension and intensity) and grouped as negative (score 0–2) and positive (score 3–6), as previously described (28, 29). Only protein expression in plasma membrane was considered for CD44, GLUT1, and CAIX analysis, while for HKII and LDHV only cytoplasmic expression was considered for further analysis.…”
Section: Methodsmentioning
confidence: 99%